2017
DOI: 10.1186/s12906-017-2050-3
|View full text |Cite
|
Sign up to set email alerts
|

Ethanolic extract of Streblus asper leaves protects against glutamate-induced toxicity in HT22 hippocampal neuronal cells and extends lifespan of Caenorhabditis elegans

Abstract: BackgroundAlthough such local herb as Streblus asper (family Moraceae) has long been recognized for traditional folk medicines and important ingredient of traditional longevity formula, its anti-neurodegeneration or anti-aging activity is little known. This study aimed to investigate the neuroprotective effect of S. asper leaf extracts (SA-EE) against toxicity of glutamate-mediated oxidative stress, a crucial factor contributing to the neuronal loss in age-associated neurodegenerative diseases and the underlyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
55
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(63 citation statements)
references
References 60 publications
8
55
0
Order By: Relevance
“…Since the HT22 cells do not express the NMDA type of glutamate receptor, toxicity in this model occurs mainly through oxytosis. In this work, our experiments were performed using a high concentration of glutamate (5 mM), which caused a 50% reduction in cell viability relative to a previous report [ 33 ]. The present study also confirmed increased ROS generation and AIF nuclear translocation as the mechanism of cell death in this model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the HT22 cells do not express the NMDA type of glutamate receptor, toxicity in this model occurs mainly through oxytosis. In this work, our experiments were performed using a high concentration of glutamate (5 mM), which caused a 50% reduction in cell viability relative to a previous report [ 33 ]. The present study also confirmed increased ROS generation and AIF nuclear translocation as the mechanism of cell death in this model.…”
Section: Discussionmentioning
confidence: 99%
“…The total flavonoid content was determined using the aluminum chloride colorimetric method modified for a microplate format as described previously [ 33 ]. In brief, 50 μL of the extract sample (1 mg/mL) was made up to 200 μL with 95% ethanol, and mixed well with 10 μL of 10% ( v /v) AlCl 3 solution and 10 μL of 1 M NaOAc solution.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After collection, the ethanolic extract of S. asper leaves was prepared as previously described [ 54 ]. In brief, the dry powered plant material (0.73 kg) was soaked in 100% ethanol (7.3 L) with a 1:10 sample-solvent ratio for 48 h at room temperature (RT) in the dark with continuous shaking.…”
Section: Methodsmentioning
confidence: 99%
“…Studies on the crude plant extract as well as the isolated compounds have demonstrated that S. asper exhibits various pharmacological properties including antioxidant, anticancer [ 47 ], antimicrobial [ 48 ], antimalarial [ 49 ], anti-filarial [ 50 ], anti-inflammation [ 51 ], and anti-hepatitis B activities [ 52 ]. Moreover, the neuroprotective properties of S. asper leaf extracts in both in vivo and in vitro models of neurodegenerative diseases were recently reported [ 53 , 54 ]. However, the active phytochemical ingredients responsible for neuroprotection have not been clearly identified.…”
Section: Introductionmentioning
confidence: 99%